Public Service Motivation: The Teaching Performance of Biology Teachers - Suhirman Suhirman; Yusuf Yusuf (Biota, 2019)
The objective of this research was to explore the impact of Public Service Motivation (PSM) on the teaching performance of biology teachers at Madrasah Aliyah in Central Lombok Regency. The research method employed was a quantitative approach. This research was conducted on 32 samples of biology teachers at Madrasah Aliyah (High School) in Central Lombok Regency. Data were collected through a structured questionnaire containing statements filled out by respondents using a Likert Scale and scores of the respondent’s answer in each variable. Statistical calculations showed that the correlation value (r) between the Public Service Motivation (PSM) and the Teachers Performance variables was positive (0.278). However, the correlation between the Public Service Motivation and the Teachers Performance variables occurred was not significant. This present study suggests that Public Service Motivation has a positive correlation with the Teaching Performance.